How Does Themis Weigh Drugs? Peculiarities of the Legal Regulation of the Determination of Quantities of Some Narcotic and Psychotropic Substances in Lithuania - Lankauskas, Mindaugas (Kriminologijos studijos, 2023)
This article delves into the legal framework concerning threshold quantities for drug offences in Lithuania and examines the potential implications of this regulation on criminal liability. It initiates by scrutinizing criminal liability for drug offences in Lithuania, with an emphasis on the legal significance of the type and quantity of specific substances. It is worth noting that existing legal acts lack defined criteria for determining small, large, or very large quantities of the narcotic and psychotropic substances. Nevertheless, the legal qualification of criminal activities and associated penalties is contingent upon the specific quantity of the drug. Furthermore, certain quantities stipulated in the Recommendations for determining small, large, and very large quantities of narcotic and psychotropic substances have raised concerns about their alignment with the latest scientific findings and empirical evidence. In light of these concerns, there is a compelling need for a review of these recommendations, guided by clearly defined and evidence-based criteria. Until such a review is conducted, the deficiencies in the existing legal regulations could be partially mitigated if courts, within the discretion granted to them, proactively exceed the quantity limits established by the recommendations.
Keywords: threshold quantities for drugs; psychoactive substances; narcotic and psychotropic substances; drug offences; threshold quantities for drugs; psychoactive substances; narcotic and psychotropic substances; drug offences; drug control